THE CONCEPT OF PEDAGOGICAL CREATIVITY IN THE PROCESS OF GLOBALIZATION - Zohidjon Shukhratovich Komilkhojayev; Nuriddinova Azizakhan Bahromjonovna (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article discusses in detail the concept of creativity in modern pedagogy, its essence, the history of its origin. Opinions about the importance of the concept of creativity today are expressed.